The Use of Describing Picture Strategy to Teach Students Speaking Skills - Peni Astuti; Hamzah, Amir (JEDLISH : Journal Of Education and English Language Teaching, 2025)
This study aimed to examine the effectiveness of the Describing Picture strategy in improving students’ speaking skills at SMK Negeri 1 Kramatwatu. A qualitative descriptive research design was employed to explore students’ and teacher’s perceptions of the strategy. The participants consisted of eleventh-grade students and an English teacher. Data were collected through classroom observations, semi-structured interviews, and documentation. The findings revealed that the Describing Picture strategy positively influenced students’ speaking skills by enhancing vocabulary development, increasing confidence, and encouraging active participation in speaking activities. The use of visual media helped students generate ideas more easily, while group work and teacher feedback reduced anxiety during oral presentations. Overall, the strategy created an engaging and supportive learning environment that facilitated students’ oral communication skills. The results suggest that the Describing Picture strategy is effective and can be applied as an alternative technique for teaching speaking in EFL classrooms.